(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Coronary Artery Bypass Grafting (CABG) is associated with a significant morbidity and mortality and several factors have been identified as predictive of complications. These include renal dysfunction and in particular renal replacement therapy. More than 600,000 coronary artery graft procedures are performed annually in the United States. Of those patients with coronary arterial disease 10% patients undergo CABG surgery. To explore the association of renal function between off-pump and on-pump-CABG. To evaluate the degree of impairment of renal function in on-pump, 80 patients (off-pump group = 50, on-pump group = 30) who underwent CABG were recruited from cardiac surgery dept. of National Heart Foundation and Research Institute Mirpur Dhaka and National Institute of Cardiovascular Disease (NICVD). Subjects were selected according to exclusion and inclusion criteria. Purpose and procedure of the study were explained in detail and informed written consent was taken from the study subjects. All the information of the study subject including history, clinical finding were recorded in a preformed data sheet. Serum urea and creatinine were significantly higher in on-pump group patients 12 hours after CABG. Serum urea was significantly higher and serum creatinine was slightly in onpump group in comparison to off-pump group. The mean urea and creatinine were found significantly higher in on-pump group in comparison to off-pump group and CCr was slightly higher lower in on-pump but not significantly decreased. DOI: http://dx.doi.org/10.3329/bjmb.v3i2.13809 Bangladesh J Med Biochem 2010; 3(2): 36-41